Single‐Cell Analysis Reveals that Vitamin C Inhibits Bone Metastasis of Renal Cancer via Cell Cycle Arrest and Microenvironment Remodeling - Jianye Zhang; Qi Zhang; Gang Lin; Ying Wang; Juan Li; Ping Wang; Jie Qi; Yuan Liang; Shiming He; Yanqing Gong; Ninghan Feng; Yang Wang; et al. (Advanced Science)
Abstract Bone metastasis is the second most common site of distant metastatic spread in renal cell carcinoma (RCC) patients, significantly contributing to cancer‐related mortality. The metastatic process is driven by both intrinsic tumor cell properties, such as cancer stem cell‐like characteristics, and the bone microenvironment. Understanding the complex interactions between cancer cells and their niche is crucial for identifying therapeutic targets to eliminate metastasis‐initiating cells and prevent overt metastasis. In this study, a murine bone metastasis model is developed using renal cancer cells derived from fibrin gel‐induced 3D tumor spheres, which exhibit stem‐like phenotypes. It is found that a stable form of vitamin C, L‐ascorbic acid 2‐phosphate sesquimagnesium (APM), significantly inhibits the growth of renal cancer stem‐like cells in vitro and the progression of RCC bone metastasis in vivo. Single‐cell RNA sequencing revealed that APM induces cell cycle arrest and reduces the metastatic potential of cancer cells. Furthermore, APM remodels the tumor microenvironment by suppressing osteoclast differentiation and neutrophil recruitment. Combining APM with a CXCR2 antagonist, SB225002, further inhibits bone metastasis progression. This study provides a high‐resolution profile of vitamin C's antitumor effects in the bone metastatic microenvironment and supports the rationale for clinical trials of vitamin C in bone metastatic RCC.